The low-carbon transition, climate commitments and firm credit risk - Sante Carbone; Margherita Giuzio; Sujit Kapadia; Johannes Sebastian Krämer; Ken Nyholm; Katia Vozian (Sveriges Riksbank, 2022)
This paper explores how the need to transition to a low-carbon economy influences credit risk. It develops a novel dataset covering firms' greenhouse gas emissions over time alongside information on strategies for managing transition risk, including climate disclosure practices and forward-looking emission reduction targets. It assesses how such metrics influence firms' credit ratings and their market-implied distance-to-default. High emissions tend to be associated with higher credit risk. But disclosing emissions and setting emission reduction targets are associated with lower credit risk, with the effect somewhat stronger for more ambitious climate commitments. After the Paris agreement, firms most exposed to transition risk also saw their ratings deteriorate relative to otherwise comparable firms, with the effect larger for European than US firms, probably reflecting differential climate policy expectations. These results have policy implications for corporate disclosures and strategies around climate change, and the treatment of climate-related transition risk in the financial sector
Keywords: C58; E58; G11; G32; Q51; Q56; 330; climate change; transition risk; disclosure; net zero; green finance; credit risk